Metode Storytelling Untuk Menanamkan Kejujuran Pada Anak Usia Dini - Nelly Agustina; Dinda Dinda; Siti Nurhaliza Novita Putri; Septia Septia (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
Storytelling is one of the learning methods that is appropriate for early childhood because it presents moral values through stories that are concrete, interesting, and easy for children to understand. Honesty is a fundamental character that should be developed from an early age to build integrity, responsibility, and positive social behavior. This study aims to analyze the effectiveness of the storytelling method in instilling honesty in early childhood and to identify supporting factors for its implementation in learning. This study employed a qualitative approach using the literature review method by analyzing various scientific publications related to storytelling, character education, and early childhood education. The collected data were analyzed using content analysis to identify concepts, patterns, and research findings relevant to the topic. The results indicate that storytelling effectively facilitates children in understanding the concept of honesty through characters, plots, and moral messages presented in stories. The method also stimulates children's cognitive, language, social-emotional, and moral development simultaneously. The effectiveness of storytelling is influenced by teachers' storytelling skills, the suitability of story content, learning media, and collaboration between schools and parents in reinforcing honest behavior in children's daily lives. Therefore, storytelling can be recommended as an innovative and meaningful learning method for developing honesty as one of the fundamental character values in early childhood education